Anatomy and histology of the gastrointestinal tract of European Starlings (Sturnus vulgaris). (1st November 2016) - North, Michelle; Movassaghi, Ahmad; Smits, Judit
There is a dearth of published data related to, or describing, the detailed anatomy and histology of the avian gut from oesophagus to cloaca, apart from that relating to commercial poultry. Without an accepted description of normal anatomy it is difficult for researchers to know whether observations in a specific population are normal or not, or for veterinarians to know what to expect during surgery or necropsy, and impedes the understanding of the remarkable adaptations among or within species. Also, as interest in the physiological role played by gut microbiota increases in avian studies, knowledge of species-specific gastrointestinal anatomy is essential. European Starlings (Sturnus vulgaris) are a prolific, well-studied invasive species across much of the world, and yet there is no information describing the anatomy of the gastrointestinal tract, or how it compares to similar species. Here, we describe the anatomy, histology and histochemistry of gastrointestinal tracts from 15 day old starlings from the proximal oesophagus to distal cloaca in order to facilitate comparison among species and different populations of the same species.